The Analysis of Factors Affecting Farmers' Accessibility Towards Markets and its Relation to Farmers' Bargaining Position - Rokhman Permadi; Lili Winarti (School of Business, Bogor Agricultural University (SB-IPB), 2018)
As the largest banana producing district in Central Kalimantan, currently most of the banana farmers in Seruyan Regency still rely on middleman to collect their crops. There are several factors that allegedly influence farmers in determining the choice of selling their crops to middleman rather than selling directly to the market. The purpose of this research is to analyze the factors that influence the accessibility of farmers to the market and to analyze the relationship between farmer's market accessibility and the bargaining position of farmers toward middleman. The respondents were farmers from the largest producer of banana kepok namely Seruyan Hilir and Seruyan Hilir Timur sub-districts. The method usedwas purposive sampling method and the data was collected in July 2017. The data were analyzed using partial structural equation model (PLS-SEM) with the main variablesare motivation, knowledge, ability to access infrastructure, bond with the middleman, involvement in farmer group, negotiation ability, market accessibility, and bargaining position of farmers. Based on the results of analysis, the knowledge, motivation, ability to access infrastructure and bond with the middleman have significant effect on the accessibility of farmers to the market. The bargaining position of farmers is significantly influenced by the accessibility of farmers to the market.